Transformasi Digital di Masa Pandemi Covid 19: Studi Fenomenologi Pada UKM Kota Medan - Suginam Suginam (Forum Kerjasama Pendidikan Tinggi, 2022)
Technology has developed very rapidly in today's era which opens the way for developments in the 4.0 revolution. The increasing role of the technology is supported by the presence of Big Data, Datamining, Internet of Things, AI and so on. The ease of access and use provided by technology causes technology to be widely used in all companies. Especially in recent years where the whole world has been hit by an outbreak of a fairly deadly disease, namely Corona Virus Disease (Covid 19). In this case, all state governments in the world have taken policies to carry out lockdowns, which means limiting all community activities, especially activities outside the home and also human interaction. Likewise for small companies such as Small and Medium Enterprises (SMEs) who also have to feel the impact of the COVID-19 pandemic which is quite great. Operational processes as well as business processes in SMEs must also be carried out using technology. Digital transformation is an expression used for changes in organizations that are influenced by technology. In the era of digital transformation, the business world is expected to be able to adapt to changes that occur and adjust its business strategy in order to maintain its competitive advantage. For SMEs themselves, digital transformation must be carried out, if not, of course, SME companies will find quite a lot of losses and can cause the company to go bankrupt. Currently, SMEs have realized that the use of technology is a key that can be used for business development. SMEs use technology to find general business-related information for the company